The Dialectic: Not just the Absolute Recoil, but the World's Living Fire that Extinguishes and Kindles Itself. Reflections on Slavoj Žižek's Version of Dialectical Philosophy in Absolute Recoil: Towards a New Foundation of Dialectical Materialism. (2014) - Fuchs, Christian
No abstract available